2015
DOI: 10.1039/c4sc02402h
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship studies of cyclopropenimines as enantioselective Brønsted base catalysts

Abstract: New insights aid in the understanding and design of cyclopropenimine-based asymmetric catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 53 publications
0
56
0
1
Order By: Relevance
“…[52] To gain ab etter understanding of the mode of action of the cyclopropenimine catalyst on the Michael addition and Mannich reactions,V etticatt, Lambert, and co-workers conducted at ransition-state analysis as well as as tudy on the structure-activity relationship. [53] Experimental 13 Ck inetic isotopic effects (KIE) provided strong evidence for their proposed mechanism of Michael addition (Scheme 23), with the carbon-carbon bond formation being the rate-determining step.F rom computed transition-state structures they concluded that the high level of enantioselectivity was not only caused by two short NH···O and OH···O interactions but also by arather unusual CH···O interaction (181,Scheme 23). Although no (H/D) KIE could be observed for this position, they assumed that this weak bond between the hydroxy group and one of the NC Cy Hg roups of the catalyst further lowers the energy of the corresponding transition states,t hus favoring them over those of the other possible pathways.…”
Section: Asymmetric Synthesis With Cyclopropenium Ionsmentioning
confidence: 99%
“…[52] To gain ab etter understanding of the mode of action of the cyclopropenimine catalyst on the Michael addition and Mannich reactions,V etticatt, Lambert, and co-workers conducted at ransition-state analysis as well as as tudy on the structure-activity relationship. [53] Experimental 13 Ck inetic isotopic effects (KIE) provided strong evidence for their proposed mechanism of Michael addition (Scheme 23), with the carbon-carbon bond formation being the rate-determining step.F rom computed transition-state structures they concluded that the high level of enantioselectivity was not only caused by two short NH···O and OH···O interactions but also by arather unusual CH···O interaction (181,Scheme 23). Although no (H/D) KIE could be observed for this position, they assumed that this weak bond between the hydroxy group and one of the NC Cy Hg roups of the catalyst further lowers the energy of the corresponding transition states,t hus favoring them over those of the other possible pathways.…”
Section: Asymmetric Synthesis With Cyclopropenium Ionsmentioning
confidence: 99%
“…While several catalytic disastereoselective methodologies have been developed for this purpose, in most of these methods, either cyclic α,β‐unsaturated carbonyl compounds, or β‐aryl‐, β‐CF 3‐ , and β‐ROCO‐substituted, acyclic α,β‐unsaturated carbonyl compounds were employed, and highly diastereoselective 1,4‐additions of conventional simple Schiff bases, of glycine esters, to β‐alkyl‐substituted α,β‐unsaturated carbonyl compounds have been little reported. Recently our group reported such 1,4‐addition reactions of glycine derivatives with acyclic β‐alkyl α,β‐unsaturated carbonyl compounds using chiral alkaline‐earth metal complexes as catalysts in the presence of a catalytic amount of a Brønsted base . In these reports, however, we noted [3+2] cycloadditions as side reactions leading to substituted pyrrolidine derivatives, and the selectivity for 1,4‐addition reactions over the cycloaddition was achieved by the use of more sterically hindered protecting groups on the amine, as well as by employing Lewis‐acidic alkaline‐earth metal complexes in homogeneous catalytic systems.…”
Section: Optimization Of Reaction Conditions For Catalytic 14‐additimentioning
confidence: 99%
“…In ihrer Studie zur Struktur‐Aktivitäts‐Beziehung von Cyclopropenimin‐katalysierter Michael‐Addition konzentrierten sich Lambert et al. auf die chirale Einheit des Katalysators und stellten fest, dass die Größe der Gruppe am stereogenen Kohlenstoffzentrum das Ergebnis der Reaktion kaum beeinflusst.…”
Section: Durch Cyclopropeniumionen Vermittelte Reaktionenunclassified